Changes in physical activity and sedentary behavior associated with an exercise intervention in depressed adults. (May 2017) - Helgadóttir, Björg; Owen, Neville; Dunstan, David W.; Ekblom, Örjan; Hallgren, Mats; Forsell, Yvonne
Abstract: Background: Exercise is beneficial for depression, but less is known about its impact on post-intervention physical activity and sedentary behavior. The aim of this paper was to determine the extent to which participation in light-, moderate- and vigorous-intensity exercise intervention influenced habitual physical activity and sedentary behavior patterns in depressed adults. Methods: Accelerometer data was collected pre- and post-intervention from depressed participants randomized to one of three 12-week intervention groups: light (n = 21), moderate (n = 25) and vigorous (n = 22) exercise. Mixed models examined changes in time spent sedentary and in light and moderate-to-vigorous physical activity (MVPA); time accumulated in sedentary and MVPA bouts; and, number of MVPA bouts and interruptions in sedentary time. Results: Overall sedentary time decreased while light activity time increased across all intervention groups but not significantly so. The light exercise intervention group reduced MVPA minutes (−8.22, 95% CI: −16.44,  −0.01), time in MVPA bouts (−8.44, 95% CI: −14.27,  −2.62), and number of activity bouts (−0.43, 95% CI: −0.77,  −0.09). The moderate exercise intervention group reduced time in MVPA bouts (−6.27, 95% CI: −11.71,  −0.82) and number of sedentary interruptions (−6.07, 95% CI: −9.30,  −2.84). No changes were observed for the vigorous exercise intervention group. Conclusions: The exercise intervention led to an increase in overall light physical activity and decrease in sedentary time, though neither change was statistically significant. Participation in the light and moderate exercise intervention groups was associated with reductions of time in MVPA bouts, but this was not evident for the vigorous exercise intervention group. Highlights: Data came from an intervention study on the effect of exercise on depression. Exercise was performed in three groups at light, moderate or vigorous intensity. We explored changes in physical activity and sedentary behavior post-intervention. Increased light physical activity and decreased sedentary time but non-significant. Reduced time in MVPA bouts in the light and moderate exercise groups.